a) 4*a - 5 = 7
4a - 5 = 7
4a = 7 + 5
4a = 12 /:4
a = 3
Sprawdzenie
4a - 5 = 7
4*3 - 5 = 7
12 - 5 = 7
7 = 7
b) 23 + 4*x = 7
23 + 4x = 7
4x = 7 - 23
4x = -16 /:4
x = -4
Sprawdzenie:
23 + 4*(-4) = 7
23 + (-16) = 7
23 - 16 = 7
7 = 7
c) 5*x - 7 + 2*x = 28
5x - 7 + 2x = 28
7x - 7 = 28
7x = 28 + 7
7x = 35 /:7
x = 5
Sprawdzenie:
5x - 7 + 2x = 28
5*5 - 7 + 2*5 = 28
25 - 7 + 10 = 28
28 = 28
d) 9*x - 7 = 3*x + 5
9x - 7 = 3x + 5
9x - 3x = 5 + 7
6x = 12 /:6
x = 2
Sprawdzenie:
9x - 7 = 3x + 5
9*2 - 7 = 3*2 + 5
18 - 7 = 6 + 5
11 = 11